COMPARISONAL STUDY OF OVERLAY THICKNESS USING MDP 2017 AND MEPDG 2015 METHODS ARIZONA CALIBRATION (CASE STUDY: BTS. KAB MAJALENGKA â BTS. KOTA PALIMANAN) - Budi Prayoga, Aldo
Roads are transportation infrastructure that connects one area to another. Roads have an important role in economic, social development and development of an area that can improve the living standard of the surrounding community. For this reason, maintenance is needed if the structural or functional ability of the road is poor, one of which is by overlaying. The overlay thickness was determined using a mechanistic-empirical method from MDP 2017 and MEPDG 2015. This study aims to compare the results of flexible pavement overlay thickness and damage models from the MDP 2017 and MEPDG 2015 methods with Arizona calibration, along with recommendations for the next steps to make MEPDG 2015 method can be used in Indonesia. Existing condition analysis was carried out by back-calculation with BAKFAA software and for mechanistic analysis using KENPAVE software to determine the reaction of the pavement structure using the MDP 2017 method. The overlay thickness calculation results showed 180 mm thick both from the MDP 2017 method and MEPDG 2015 Arizona calibration with control determining damage in the form of fatigue cracking. The results of the comparison of damage models show that the MEPDG 2015 damage model has several additional variables and there are local and global calibration variables as adjustment factors. The damage model in the MDP 2017 method only consists of a structural damage model, while in the MEPDG 2015 method there is a functional damage model using the IRI value. The application of the MEPDG 2015 method in Indonesia is still requires a lot of studies, especially on the completeness of traffic data, climate, and material properties which in this study are made into the flowchart of the MEPDG method adjustment plan with the modification of the damage model and the determination of performance criteria according to conditions in Indonesia. The initial application of the MEPDG 2015 method in Indonesia can be done by calibrating the empirical model using the Arizona calibration value as the basis for existing road projects in Indonesia.